2019
DOI: 10.1111/php.13080
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Me45 Melanoma Cells Increase Damaging Effect in UVC‐irradiated Cells

Abstract: The aim of our study was to investigate the possible mechanism(s) of the bystander effect induced by UVC light in malignant melanoma Me45 cells that were co-incubated with irradiated cells of the same line. We have found that the UVC band effectively generated apoptosis, premature senescence, single and double DNA strand breaks and reduced clonogenic survival of bystander cells. However, in the feedback response, the bystander cells intensified damage in directly irradiated cells, especially seen at the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Similar phenomenon can be observed in UV radiation as well (Eftekhari and Fardid, 2019). Krzywon and Widel (2019) found that viability of non-irradiated cells would be reduced when coincubated with irradiated cells. Induction of cell-cycle arrest at the G2/M transition was observed in nonirradiated cells treated with conditioned medium from UVCirradiated A375 human melanoma cells (Ghosh et al, 2013).…”
Section: Introductionsupporting
confidence: 77%
“…Similar phenomenon can be observed in UV radiation as well (Eftekhari and Fardid, 2019). Krzywon and Widel (2019) found that viability of non-irradiated cells would be reduced when coincubated with irradiated cells. Induction of cell-cycle arrest at the G2/M transition was observed in nonirradiated cells treated with conditioned medium from UVCirradiated A375 human melanoma cells (Ghosh et al, 2013).…”
Section: Introductionsupporting
confidence: 77%
“…In further studies, potential p42/44 ERKs-, AKT-and p38-mediated phosphorylation of ERα in UVC-treated cells is to be investigated. UV irradiation has been indicated to stimulate the bystander effect (48), with corresponding events such as apoptosis, premature senescence, single and double DNA strand breaks, and reduced clonogenic survival described in bystander cells (49).…”
Section: Discussionmentioning
confidence: 99%